ROLE OF MONOTHERAPY ALPHA BLOCKERS VERSUS COMBINATION ALPHA BLOCKERS AND ANTICHOLINERGICS IN THE MANAGEMENT OF LOWER URINARY TRACT SYMPTOMS/BENIGN PROSTATIC HYPERPLASIA - Sajid, Muhammad Tanveer; Akmal, Muhammad; Khan, Imran; Nawaz, Muhammad; Shahzad, Khubaib; Ahmad, Hussain (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the mean international prostate symptom score between monotherapy (alpha blockers) versus combination therapy (alpha blockers plus cholinergic antagonist) in the management of lower urinary tract symptoms due to benign prostatic hyperplasia. Study Design: Quasi experimental study. Place and Duration of Study: Armed Forces Institute of Urology Rawalpindi, from Sep 2018 to Feb 2019. Methodology: One hundred and sixty male patients, who presented with lower urinary tract symptoms secondary to benign prostatic hyperplasia with prostate size up to 70 grams were enrolled. Patients in group I received Tamsulosin 0.4 mg OD + placebo while those in group II received Tamsulosin 0.4 mg OD + Solifenacin 5mg OD for 4 weeks. Baseline and Post 04weeks’ treatment international prostate symptom score was recorded and analyzed. Results: Mean age of presentation in group I was 57.44 ± 8.74 years while in group II, it was 56.43 ± 8.98 (p=0.47). Baseline characteristics were similar in both groups. Baseline international prostate symptom score was 19.11 ± 7.93 in group I and 20.01 ± 8.18 in group II respectively (p=0.49). In group I, mean international prostate symptom score at 4 weeks was 16.71 ± 7.86 and in group II, it was 12.48 ± 8.04 (p-value <0.001), implying that international prostate symptom score was significantly lower in group II in comparison with group I at 4 weeks. Conclusion: Statistical significant difference of combination therapy of α-blocker and antimuscarinic compared with α-blocker monotherapy was observed in the present study.